Educação permanente na saúde da família mediada por tecnologias de educação à distância: um estudo de caso - Ferreira, Julyenne Dayse de Oliveira (2023)
Introduction: The Family Health Continuing Education Program is a health training strategy for professionals working in the Family Health Strategy. It results from the partnership between the Ministry of Health and the Federal University of Rio Grande do Norte as a strategy to support and strengthen Primary Health Care. Objective: To analyze the use of the Distance Learning modality in the Permanent Education Program in Family Health related to Permanent Education in Health. Methodology: this is a case study with a qualitative approach using the online questionnaires on the course Platform as instruments, answered by 206 medical professionals. The analysis of the narratives was carried out through thematic content analysis according to Minayo. The study followed the criteria for research involving human beings with approval by the ethics and research committee of the University Hospital Onofre Lopes of the Federal University of Rio Grande Do Norte - HUOL/UFRN according to opinion n°3.996.389. Results: Technologies can still be a problem in some extremes of Brazil. The Permanent Education Program in Family Health sparked a movement to consolidate Permanent Education in the educational processes carried out to train professionals in the Unified Health System, especially in primary care. It allowed for discussion among professionals on topics that emerged in their daily work, resulting in an exchange of experiences among the team, which contributes to updating technical knowledge and providing changes in professional practices. Conclusion: The Distance Learning modality of the Permanent Education Program in Family Health is configured as a strong permanent education strategy, contributing to the advancement of the teaching-learning process in the Unified Health System.